PREVALENCE OF SKIN DISEASES IN THE COASTAL AREA OF TELUK NIBUNG NORTH SUMATRA - Izzah Dienillah Saragih; Tri Niswati Utami; Fitriani Pramita Gurning (Proceedings of the International Conference on Applied Science and Health, 2019)
Background: In an observational study of The Global Burden Disease stated skin diseases contributed to 1.79% of lost productive days worldwide due to itching, scratching, or secondary infections which accompanying. Skin diseases are among the three biggest diseases in Tanjung Balai City with 7.230 cases in 2017. Tanjung Balai is a coastal region on the East Coast of North Sumatra with Teluk Nibung as the largest Subdistrict which had characteristics of tropical climates, high density, the lack of basicsanitation and personal hygiene and it caused the population susceptible to skin diseases.The study is to find out the prevalence of skin diseases in Teluk Nibung2018. Methods:This was an observational study using data sourced from surveillance of infectious diseases in Teluk Nibung Health Center regarding the 10 biggest diseases in the one Primary Health Care (Puskesmas) in 2018. The study was conducted in April 2019. Data were analyzeddescriptivelyusing univariate analysis with table and graphs of skin diseases frequency and distribution Results: Skin disease wasthe third largest disease in Teluk Nibung Subdistrict with 2.208 casesin 2018. Disease trends increased throughout 2018 with significantly increased in May. The proportion of skin diseases wasbigger among the female group, which is 56%. The environmental conditions in Teluk Nibung reflected coastal areas with high-density population, unhealthy settlement conditions, and the lack of basic sanitation and personal hygiene. Conclusions:Skin Disease is still a major health problem in Teluk Nibung due to the climate, weather, and the lack of environmental health factor. It needsfor researchers conducted research on skin diseases related to basic sanitation, personal hygiene among society in the coastal area and stakeholders need to create policy improved health environment. Keywords: Skin disease, coastal area, North Sumatra